Pharmacokinetics and pharmacodynamics of nab‐paclitaxel in patients with solid tumors: Disposition kinetics and pharmacology distinct from solvent‐based paclitaxel. (9th April 2014) - Chen, Nianhang; Li, Yan; Ye, Ying; Palmisano, Maria; Chopra, Rajesh; Zhou, Simon
Abstract The aim of this study was to characterize population pharmacokinetics and the exposure–neutropenia relationship with nanoparticle albumin‐bound (nab)‐paclitaxel in patients with solid tumors. Plasma and blood concentrations of paclitaxel and neutrophil data were collected from 150 patients with various solid tumors over the nab‐paclitaxel dose range of 80–375 mg/m2. Data were analyzed using nonlinear mixed‐effect modeling or logistic regression. Pharmacokinetics of nab‐paclitaxel were described by a 3‐compartment model with saturable distribution and elimination. The rapid disappearance of circulating paclitaxel was driven by its fast distribution to peripheral compartments; maximum rate for saturable distribution (325000 μg/h) was 40‐fold greater than that for saturable elimination (8070 μg/h). Albumin was a significant covariate of paclitaxel elimination (P < .001), while total bilirubin, creatinine clearance, body size, age, sex, and tumor type had no significant or clinically relevant effect. The probability of experiencing a ≥50% reduction in neutrophils was best correlated to the duration above the drug concentration of 720 ng/mL. At a given exposure level, neutropenia development was positively correlated with increasing age but not significantly influenced by hepatic function, tumor type, sex, or dosing schedule. Covariate analyses supports exposure‐matched dose adjustments in patients with moderate to severe hepatic impairment.